The significance of cross-fertilisation practices in Kiswahili technical and specialised translations (Journal for Studies in Humanities and Social Sciences, 2017)
As opposed to interpreters of verbal communication, translators of written texts have ample time for consulting, revising, reviewing, discussing, weighing and editing. That means cross-fertilisation with fellow translators, speakers of the language, subject experts, clients as well as text reviewers and/or editors helps them improve the translation process and minimize errors in the final translation. This paper is a practical study of English – Kiswahili translations aimed at showing that collaborative efforts across individuals, organisations, and institutions both locally and internationally can improve the overall translation process and product. The data for this study was collected through observation, documentary review as well as through interview and was then analysed through a comparative method. The discussion draws experience from legal and technical (i.e. computer and web-based) translation into Kiswahili, and further emphasizes that there are areas of improvement in Kiswahili translation and training for time and cost effectiveness. The paper argues that despite the importance of cross-fertilisation in the translation process, Kiswahili translators need to improve their expertise to include specialisations in certain fields.